Attentional biases in patients with alcohol dependence: influence of coexisting psychopathology. (November 2016) - Sinclair, Julia M.A.; Garner, Matthew; Pasche, Sonja C.; Wood, Thomas B.; Baldwin, David S.
Abstract: Objective: The effects of coexisting psychopathology on disorder‐specific attentional biases in patients with alcohol dependence are uncertain. We undertook a cross‐sectional study assessing attentional biases to alcohol‐, depression‐, and anxiety‐ related stimuli using the visual probe task in patients with alcohol dependence, attending a community alcohol service. Methods: Using the visual probe task, we presented disorder‐specific words (relating to alcohol, anxiety, and depression) for 500 ms and measured reaction times. Results: Participants demonstrated a significant attentional bias towards alcohol‐related cues (mean 8.5, p  = 0.03) but significant avoidance of depression‐related cues (mean −8.4, p  = 0.01). The subgroup of participants who were recently abstinent ( n  = 70) showed greatest avoidance of depression‐related cues ( t (69) = 2.68, p  < 0.01) but no significant vigilance towards alcohol or anxiety cues, whereas those still drinking ( n  = 43) showed attentional biases towards alcohol‐related ( t (42) = 2.70, p  = 0.01) and social anxiety‐related cues ( t (42) = 2.84, p  < 0.01). In the whole sample, the magnitude of attentional bias to alcohol was not correlated with length of drinking history, number of comorbid conditions, or severity of anxiety/depression. Conclusions: In a clinical sample of alcohol‐dependent patients, further investigation is required to explore whether these attentional biases reflect current drinking status or factors indicating prognosis.